Difference, dissonance, and redemption in sport heritage: interpreting the tangled legacy of Pete Rose at two museums. Issue 2 (3rd March 2020) - Ramshaw, Gregory; Gammon, Sean
ABSTRACT: Induction into a hall of fame can be the ultimate accolade for an athlete. Arguably, the most famous of all sport halls of fame is the National Baseball Hall of Fame and Museum (NBHF) in Cooperstown, New York. The NBHF is widely considered the primary authority concerning baseball enshrinement, although other baseball halls of fame may differ in their assessment of particular players. One such case involves Pete Rose, baseball's all-time hits leader, who received a lifetime ban from Major League Baseball for gambling on his own games. Rose is omitted for consideration for the NBHF, however he is an inductee at the Reds Hall of Fame and Museum (RHFM) in Cincinnati, Ohio where he was a star player. Major League Baseball and the Office of the Commissioner are the authorizing agents for both halls of fame and appear to support both perspectives. This research note explores the different approaches to Pete Rose at the NBHF and the RHFM. We consider the potential for dissonant narratives to be used as a management tool by the authorizing agent in order to gauge public opinion and assuage Rose's fans whilst keeping the debate firmly in the public eye.